DASAR-DASAR PEMIKIRAN FILSAFAT ADVAITA VEDĀNTA ADI ŚAṄKARĀCĀRYA SEBAGAI CAHAYA KECERDASAN MENUJU KESADARAN KETUHANAN - Prasanthy Devi Maheswari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Lately, it's easier to spread hate speech, the loss of humanity and human concern for the universe, this indicates the world is not fine and far from harmony. Seeing this phenomenon, it is interesting to examine the philosophical thoughts initiated by a philosopher Adi Śaṅkarācārya who is known as Advaita Vedānta. Advaita means no dualism. The Advaita Śaṅkarācārya system denies the existence of more than one reality. Brahman is the only reality that exists. Nature is an appearance or illusion of Brahman but reality is relative. While the individual/jiva/personal spirit is no different from Brahman but in reality it is also relative because it is caused by the fetters of avidya and manifests itself with the additional means of upadhi. This study tries to describe the basic concept of Advaita Vedānta in the vakya (speech) Upaniṣad in the present life. This becomes one of the ways to achieve divine awareness in realizing the Self by seeing everything is Brahman.